Case Report: Rectal Resection and Anastomosis Method as Rectal Prolapse Treatment in Persian Kitten - Indra, Rusmin; Jayawardhita, Anak Agung Gde; Pemayun, I Gusti Agung Gde Putra (Indonesia Medicus Veterinus, 2019)
Rectal prolapse is a protrusion or eversion of the rectal mucous membrane from the anus. Prolapse generally occurs in young and old animals caused by relaxation of spinchter ani . A kitten was examined at the Udayana University Animal Hospital with complaints of recurrent prolapse, good appetite, and hyperactive. Physical and haematological examination showed that the kitten is proper to get surgery. Kitten being surgery with rectal resection method for rectum which got ulceration, then anastomosis is performed on remaining parts. Around the anus was sutured with a purse string technique. Post surgery treatment is carried out by fluid therapy, antibiotics and anti-inflammatory drugs. The wound was healed on the fifth day after surgery and prolapse does not occur again.